Tratamento crônico com tamoxifeno de maneira dose-dependente afeta a memória e os fenótipos do tipo ansioso e depressivo em ratas Wistar intactas - Klann, Isabella Pregardier (2022)
Tamoxifen, a selective estrogen receptor modulator, the gold standard for adjuvant therapy of breast cancer, has dichotomous effects on memory, anxious- and depressive-like phenotypes described in the literature. Studies with intact female rats are necessary to understand Tamoxifen’s per se effects on a protocol that mimics humans’ therapy, 20 mg per day for 5 years. This dissertation evaluated Tamoxifen’s chronic effects on memory, anxious- and depressive-like phenotypes in intact female Wistar rats. In addition, to evaluate Tamoxifen’s effects on hippocampal mechanisms. Intact female Wistar rats (60 days) were treated with Tamoxifen (0.25 and 2.5 mg/kg) by the intragastric route for 59 days. After treatment, animals were subjected to behavioral tests, divided into two experimental sets. Subsequently, the animals were euthanized and samples of hippocampus, uterus, and plasma were collected. The results of manuscript I demonstrate that Tamoxifen at a dose of 0.25 mg/kg decreased animals’ performance in the object location test and in the short-term memory of the object recognition test. The decrease in the hippocampal levels of pro and mature brain-derived neurotrophic factor (BDNF) and the ratio of phosphorylated CAMP response element-binding (CREB) protein/total were found in rats treated with 0.25 mg. Tamoxifen at a dose of 2.5 mg/kg decreased animals’ performance in the object location test and in the object recognition test (short- and long-term memory), decreasing the hippocampal levels of BDNF, CREB, and the ratios of phosphorylated serine/threonine-protein kinase (ERK)/total and phosphorylated extracellular signal-regulated kinase (Akt)/total. Furthermore, levels of tropomyosin receptor kinase B (TRKB) were not altered by both Tamoxifen doses. The estrous cycle phases distribution was different only in the post-natal day 122 and the locomotor activity was not altered. The results of manuscript II reveal that the lowest Tamoxifen dose induced anxious-/depressive-like and apathy behaviors, and modulated hippocampal apoptosis, with increasing of Bcl-2 associated protein X (BAX) and p75 neurotrophin receptor p75NTR (pro-apoptotic proteins) and decreasing of B-cell lymphoma protein 2 (Bcl2) (anti-apoptotic proteins). The highest dose of Tamoxifen induced depressive-like, anhedonia, and apathy behaviors in female rats. This dose increased the levels of plasma corticosterone, hippocampal glucocorticoid receptor (GR), inhibitory protein kappa B alfa (IKKB), IKB kinase protein alpha (IKB), nuclear factor kappa B (NF-kB), cyclooxygenase2 (COX2), interleukin-1β (IL-1β), and inflammasome NLRP3). The levels of interleukin-10 (IL-10) were increased, but those of tumor necrosis factor alpha (TNFα) were not altered by both Tamoxifen doses. Tamoxifen at both doses altered locomotor activity of rats. The estrous cycle phases distribution was altered and uterus’ relative weight was decreased. In conclusion, Tamoxifen, in a dose-dependent manner, affected memory, anxious- and depressive-like phenotypes and hippocampal proteins.